Biosolubilisasi Lignit Mentah Hasil Iradiasi Gamma dan oleh Trichoderma asperellum - Sugoro, Irawan; Astuti, Dea Indriani; Sasongko, Dwiwahju; Aditiawati, Pingkan (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
Biosolubilization is a promising technology for converting solid coal to liquid oilby addition of microorganism. Aim of this research is to compare between gamma irradiatedlignite (10 kGy) with raw lignite in biosolubilization by selected fungi Trichoderma asperellum.Treatments were A (MSS + gamma irradiated lignite 5% + T. asperellum) and B (MSS + rawlignite 5% + T. asperellum) with sub-merged culture. There were two parameters observed i.e.biosolubilization product based on absorbance value at 250nm and 450nm and metal analysis byneutron activation analysis (NAA). The highest biosolubilization will be analyzed by FTIR andGCMS. The results showed that biosolubilization of raw lignite (B) was higher than sterilizedlignite (A) based on absorbance value at 250nm and 450nm. The metal of lignite was decreasedafter incubation. FTIR analysis showed that both of treatment had similar spectra onbiosolubilization products. GCMS analysis showed that both of treatment had differentnumber of hydrocarbon, i.e. C6 — C35 (A) and C10 — C35 (B) and dominated by aromatic acids aliphatic and phenylethers. Both of treatment product had the potency as oil substituted butits recommended to deoxygenate for higher quality.